Human Recombinant Peptide Sponge Enables Novel, Less Invasive Cell Therapy for Ischemic Stroke - Michiyuki Miyamoto; Kentaro Nakamura; Hideo Shichinohe; Tomohiro Yamauchi; Masaki Ito; Hisayasu Saito; Masahito Kawabori; Toshiya Osanai; Tasuku Sasaki; Kiyohiro Houkin; Satoshi Kuroda (Hindawi Limited, 2018)
Bone marrow stromal cell (BMSC) transplantation has the therapeutic potential for ischemic stroke. However, it is unclear which delivery routes would yield both safety and maximal therapeutic benefits. We assessed whether a novel recombinant peptide (RCP) sponge, that resembles human collagen, could act as a less invasive and beneficial scaffold in cell therapy for ischemic stroke. BMSCs from green fluorescent protein-transgenic rats were cultured and Sprague-Dawley rats were subjected to permanent middle cerebral artery occlusion (MCAo). A BMSC-RCP sponge construct was transplanted onto the ipsilateral intact neocortex 7 days after MCAo. A BMSC suspension or vehicle was transplanted into the ipsilateral striatum. Rat motor function was serially evaluated and histological analysis was performed 5 weeks after transplantation. The results showed that BMSCs could proliferate well in the RCP sponge and the BMSC-RCP sponge significantly promoted functional recovery, compared with the vehicle group. Histological analysis revealed that the RCP sponge provoked few inflammatory reactions in the host brain. Moreover, some BMSCs migrated to the peri-infarct area and differentiated into neurons in the BMSC-RCP sponge group. These findings suggest that the RCP sponge may be a promising candidate for animal protein-free scaffolds in cell therapy for ischemic stroke in humans.